Viscoelastic parameters of invasive breast cancer in correlation with porous structure and elemental analysis data. (November 2021) - Mojra, Afsaneh; Hooman, Kamel
Highlights: The novelty of studying mechanical behavior of the most aggressive type of breast cancer. The novelty of studying the behavior of invasive ductal carcinoma at tissue scale. Characterization of breast cancer through determination of early and late relaxation times. The novelty of correlating mechanical behavior with microstructure and elemental composition. Statistical analysis on the relationship between malignancy indicators and material parameters. Abstract: Background and objective: Invasive ductal carcinoma (IDC) is the most common and aggressive type of breast cancer. As many clinical diagnoses are concerned with the tumor behavior at the compression, the IDC characterization using a compression test is performed in the present study. In the field of tissue characterization, most of the previous studies have focused on healthy and cancerous breast tissues at the cellular level; however, characterization of cancerous tissue at the tissue level has been under-represented, which is the target of the present study. Methods: Throughout this article, 18 IDC samples are tested using a ramp-relaxation test. The strain rate in the ramp phase is similar for all samples, whereas the strain level is set at 2, 4 and 6%. The experimental stress-time data is interpolated by a viscoelastic model. Two relaxation times, as well as the instantaneous and long-term shear moduli, are calculated for each specimen. Results: The results show that the long-term and instantaneous shear moduli vary in the range of 0.31–17.03 kPa and 6.03–55.13 kPa, respectively. Our assessment of the viscoelastic parameters is accompanied by observing structural images of the IDCs and inspecting their elemental composition. It is concluded that IDCs with lower Magnesium to Calcium ratio (Mg:Ca) have smaller shear modulus and longer relaxation time, with a p -value of 0.001 and 0.01 for the correlation between Mg:Ca and long-term shear modulus, and Mg:Ca and early relaxation time. Conclusions: Our identification of the IDC viscoelastic parameters can contribute to the IDC inspection at the tissue level. The results also provide useful information for modeling of breast cancer. Graphical abstract: Image, graphical abstract